Analisis Implementasi Manajemen Program Imunisasi Hepatitis B-0 di Wilayah Kerja Puskesmas Rumbio Jaya Kabupaten Kampar Tahun 2020 - Ejon asmanto; Syafrani Syafrani; Yanwir Kamal; Ahmad Hanafi; Dedi Sambudi (Jurnal Kesehatan Komunitas, 2021)
The implementation of immunization program is a very important element, but still found that the immunization program at health center is not run in accordance with a promise that is in Indonesian Permenkes No. 12 in 2017. This study aims to analyze the program management immunization Hepatitis B-0 in the work area Rumbio Jaya Health Center in Kampar Regency in 2020. This research used is qualitative research with a descriptive approach. This data collection was carried out at the Rumbio Jaya Health Center in Kampar Regency through in-depth interviews involving 7 informants and reviewing documents.The results showed that there was no vaccine management officer, immunization training had not been carried out, planning for syringe, safety box, and cold chain planning was not carried out by the Rumbio Jaya Health Center, unavailability of immunization waste management and timely immunization reporting. It is recommended to Rumbio Jaya Health Center in Kampar Regency should appoint vaccine management officers so that immunization activities can be carried out optimally, it is better to plan syringe, safety box and cold chain needs, it is better to make the imunization reporting at the fifth date the following month. It is recommended to the Rumbio Jaya Health Office conduct minimum immunization training once a year and should provide immunization waste management places.